Quantum many-body physics in open systems : measurement and strong correlations : doctoral thesis accepted by the University of Tokyo, Tokyo, Japan /: doctoral thesis accepted by the University of Tokyo, Tokyo, Japan. ([2020]) - Ashida, Yuto
No abstract available